Pasos en el camino hacia mejoras en la formación inicial docente en la carrera Licenciatura en Educación y Pedagogía en Educación Diferencial en Problemas de Aprendizaje (Educational Perspectives Magazine (REPED), 2022)
From the year 2006 on, a team of teachers of the Bachelor Programme in Education and Special Education Teaching in Leaming Disabilities of UMCE has been developing a line of research entitled “Improvement of Initial Teacher Training (ITT)”. In this respect, a first investigation carried out was named “The Competencies of the Special Education Teacher of Learning Disabilities in the context of the implementation of decree n° 291. FD3AS project 10/06, sponsored by DIUMCE (2006-2007).Considering the results obtained in the first investigation of the line of research on the one hand, and the importance that the practical procedures in the development of certain competencies, on the other, it was considered fundamental to carry out a second study to enhance the final practicum.The investigation was entitled “Practicum Supervisión as a Tool to Improve Initial Teacher Training”, FIBAS project 10/08, sponsored by DIUMCE (2008-2009). This article corresponds to a synthesis of the main results obtained in both investigations.